Advance, Retreat, and Halt of Abrupt Gravel‐Sand Transitions in Alluvial Rivers. Issue 19 (13th October 2017) - Blom, Astrid; Chavarrías, Víctor; Ferguson, Robert I.; Viparelli, Enrica
Abstract: Downstream fining of bed sediment in alluvial rivers is usually gradual, but often an abrupt decrease in characteristic grain size occurs from about 10 to 1 mm, i.e., a gravel‐sand transition (GST) or gravel front. Here we present an analytical model of GST migration that explicitly accounts for gravel and sand transport and deposition in the gravel reach, sea level change, subsidence, and delta progradation. The model shows that even a limited gravel supply to a sand bed reach induces progradation of a gravel wedge and predicts the circumstances required for the gravel front to advance, retreat, and halt. Predicted modern GST migration rates agree well with measured data at Allt Dubhaig and the Fraser River, and the model qualitatively captures the behavior of other documented gravel fronts. The analysis shows that sea level change, subsidence, and delta progradation have a significant impact on the GST position in lowland rivers. Key Points: Even a limited gravel supply to a river sand bed reach results in the formation of a gravel‐sand transition (GST) A GST migrates more slowly as the gravel reach lengthens. It can halt under base level rise, subsidence, or delta progradation We propose analytical formulations for the GST migration celerity and the stable GST position